If $\int\limits_0^x\{t\} d t=\int\limits_0^{\{x\}} t d t$ (where $x>0, x \notin Z$ and {.} represents fractional part function), then |
$x \in(0,1)$ $[x]=1$ $x \in(1,6)-I$ none of these |
$x \in(0,1)$ |
Let $x \in(k, k+1)$, where $k \in Z$. Then, $\int\limits_0^x\{t\} d t=\int\limits_0^{\{x\}} t d t$ $\Rightarrow \int\limits_0^k(t-[t]) d t+\int\limits_k^x(t-[t]) d t=\int\limits_0^{\{x\}} t d t$ $\Rightarrow \sum\limits_{r=1}^k \int\limits_{(r-1)}^r(t-[t]) d t+\int\limits_k^x(t-[t]) d t=\frac{1}{2}\{x\}^2$ $\Rightarrow \sum\limits_{r=1}^k \int\limits_{(r-1)}^r\{t-(r-1)\} d t+\int\limits_k^x(t-k) d t=\frac{1}{2}\{x\}^2$ $\Rightarrow \frac{1}{2} \sum\limits_{r=1}^k\left[-\{t-(r-1)\}^2\right]_{r-1}^r+\left[\frac{1}{2}(t-k)^2\right]_k^x=\frac{1}{2}\{x\}^2$ $\Rightarrow \sum\limits_{r=1}^k 1+(x-k)^2=\{x\}^2$ $\Rightarrow k+(x-k)^2=(x-k)^2$ $[∵ x \in(k, k+1) ∴ \{x\}=x-k]$ $\Rightarrow k=0$ ∴ $x \in(0,1)$ |